1982
DOI: 10.1111/j.1432-1033.1982.tb05883.x
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR Studies of the Binding of Bacteriophage‐M13‐Encoded Gene‐5 Protein to Oligo(deoxyadeny1ic acid)s of Varying Length

Abstract: The binding of gene-5 protein to oligo(deoxyadeny1ic acid)s varying in length from 2 to 16 nucleotides has been studied by titrating the protein with the oligonucleotides and recording the 'H NMR spectra at 360 MHz. To obtain information about the mode of binding of the protein the aromatic parts of the spectra have been analysed by performing spectral simulations, starting from the assignments obtained from nuclear Overhauser enhancements at 500 MHz [Alma, N. C. M., Harmsen, B. J. M., Hull, W. E., Van der Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
39
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 30 publications
(34 reference statements)
7
39
1
Order By: Relevance
“…The aromatic residues Y26, Y34, and Y41 of one monomer and F73 of the opposite monomer in the dimer are involved in the binding by stacking with the bases of the nucleic acid. The residues R16, R21, R80 and K46 were believed to be involved in the binding by ionic interactions with the phosphate moieties of the nucleic acid.In solution the structure of gVp and of its complex with oligonucleotides has been studied extensively by means of 'H-NMR techniques [13,. These experiments have shown that the structure of these complexes is different from the structure proposed by Brayer and McPherson.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The aromatic residues Y26, Y34, and Y41 of one monomer and F73 of the opposite monomer in the dimer are involved in the binding by stacking with the bases of the nucleic acid. The residues R16, R21, R80 and K46 were believed to be involved in the binding by ionic interactions with the phosphate moieties of the nucleic acid.In solution the structure of gVp and of its complex with oligonucleotides has been studied extensively by means of 'H-NMR techniques [13,. These experiments have shown that the structure of these complexes is different from the structure proposed by Brayer and McPherson.…”
mentioning
confidence: 99%
“…In solution the structure of gVp and of its complex with oligonucleotides has been studied extensively by means of 'H-NMR techniques [13,. These experiments have shown that the structure of these complexes is different from the structure proposed by Brayer and McPherson.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The assignments obtained for GVP Y41H can thus be used to identify amino acid proton resonances of the wild-type molecule to evaluate for example the effects of oligonucleotide binding [26]. Small but significant differences in a-resonance chemical shifts ( > 0.03 and < 0.12 ppm) between the two molecules were observed for residues 39,40,42 and 43.…”
Section: Fig 2 Sequence Of M I 3 Cvp Y4ih With a Summary Of The Shomentioning
confidence: 99%